Pioneers of modern brain research—Cécile and Oskar Vogt and the Nobel Prize - Hansson, Nils; Fangerau, Heiner; De Sio, Fabio; Grell, Ursula; Amunts, Katrin (Frontiers in Neuroanatomy, 2025)
This article explores the complex and ultimately unsuccessful Nobel Prize trajectories of Oskar (1870–1959) and Cécile Vogt (1875–1962), as well as their ongoing scientific legacy. Their legacy sheds light on the background to the decision from different perspectives. Despite multiple nominations, the couple never received the Nobel Prize in Physiology or Medicine. Drawing upon archival sources from the Nobel Forum and the Vogt Archive in Düsseldorf, we reconstruct the history of their candidacies, the reasons why they were proposed, and those behind the committee’s repeated rejections. Their work on cyto- and myeloarchitectonics, the functional anatomy of the basal ganglia, and structure–function relationships in the cerebral cortex earned them international recognition. However, the Nobel Committee remained unconvinced, often citing issues of scientific priority, insufficient novelty, and the controversial nature of some of their claims. Despite their exclusion from the prize, the Vogts’ research shaped the development of brain science across Europe and beyond, influencing later Nobel laureates and contributing to foundational concepts in neuroanatomy and -physiology. Their case invites reflection on the historical contingencies of scientific recognition and the shifting criteria for what counts as a “discovery” worthy of the Nobel Prize.